COMPARATIVE ANALYSIS OF CLASSICAL MESSAGE FLOW ANDINTEGRATION OF QUANTUM TECHNOLOGIES INTO MESSAGETRANSMISSION USING QISKIT LIBRARY - Demeuov, Daulet (Journal of Emerging Technologies and Computing, 2024)
The issue of secure connectivity is becoming increasingly common these days. Practically all encryption methods can be hacked, prompting the development of a data transport that is impenetrable. This scientific paper discussed the way of classic transmission of information and integration of quantum technologies into this network in order to increase the safety of the channel. This paper includes information about work done on research, such as learning principles of quantum cryptography technologies, basic logical gates and key terms such as superposition, entanglement and teleportation. Qubits are formed and exchanged between 2 parts of the Local Area Network (LAN) using Qiskit library. 2 protocols of data transmission: classic and quantum have been analyzed and compared.